Hostel Management System Using Image Recognition - Mensah, Yaw A.; Olasubomi, Odekunle; N, Ogbonnaya-Orji Chinatu-; Judah, Olaobaju; Jonah, Joshua (Engineering And Technology Journal, 2022)
Hostel management system is an advanced system that makes organizing the affairs of the hostel quicker, simpler, and more efficient. The normal procedure of allocating hostels at Babcock University involves selecting the preferred hostel online via the UMIS (University management information system) portal while the procedure for selecting rooms involves students showing up physically in school with their evidence of school fees payment. Due to these, it is undeniable that it is extremely time-consuming with an unreliable method of storing relevant documents and requires a lot of human resources. This proposed hostel management system is a web application developed using C# programming language. This application includes a module that finds missing items, a module for hostel registration and also a module for giving feedback. In conclusion the model has made managing the affairs of the hostel easy.